Treatment Outcome of External Auditory Canal Carcinoma: The Utility of Lateral Temporal Bone Resection - Kohei Saijo; Kohei Saijo; Yushi Ueki; Ryoko Tanaka; Yusuke Yokoyama; Jo Omata; Takeshi Takahashi; Hisayuki Ota; Ryusuke Shodo; Keisuke Yamazaki; Takafumi Togashi; Ryuichi Okabe; et al. (Frontiers in Surgery, 2021)
We examined the role of lateral temporal bone resection (LTBR) in the treatment of external ear canal (EAC) carcinoma between 2007 and 2018. The estimated 3-year disease-free survival (DFS) and disease-specific survival (DSS) according to the tumor stage and treatments were investigated in 36 patients with EAC squamous cell carcinoma. T stage classification according to the University of Pittsburgh staging system was as follows: 14 patients in T1, four patients in T2, nine patients in T3, and nine patients in T4. The 3-year DFS rate was 77.4% for T1 tumors, 100% for T2, 44.4% for T3 tumors, and 11.1% for T4 tumors (p < 001). The 3-year DSS rate was 100% for T1/T2 tumors, 87.5% for T3 tumors, and 11.1% for T4 tumors (p < 0.01). T1/T2 patients received mostly LTBR. Among nine T3 tumors, five patients (56%) received LTBR combined with preoperative chemotherapy and/or postoperative radiation (RT). Four of them had negative surgical margin and survived with no evidence of disease. The DFS of T3 patients who underwent concurrent chemoradiotherapy and LTBR was 0 and 80%, respectively (p = 0.048). For T1/T2 tumors, surgery achieved an excellent outcome. For T3 tumors, LTBR achieved negative surgical margin and showed good survival when combined with preoperative chemotherapy and/or postoperative RT. In contrast, the prognosis of T3 patients who could not undergo surgery was as poor as that of T4 patients. Therefore, in addition to subtotal temporal bone resection, LTBR-based treatment strategy may be a treatment option for limited cases of T3 patients.